Treatment of depression in adolescents and adults - Springer, David W.; Rubin, Allen; Beevers, Christopher G. (Hoboken, N.J. : Wiley, 2011)
'Mental health practitioners are increasingly forced to use evidence-based practices by third-party providers. However, studies have shown practitioners rarely use evidence-based practices because of difficulties obtaining training and expertise. This volume in the Clinician's Guide to Evidence-Based Practice Series provides clinicians with a beginning level of understanding in evidence-based practice for depression in a manner that fits clinician time constraints. Forgoing the typical academic approach for a more user-friendly'how-to' and'what-now' style, the book is an easy-to-use and essential resource for practitioners and students-in-training'--
Includes bibliographical references and indexes.
Keywords: Depression in adolescence -- Treatment; Evidence-Based Medicine; PSYCHOLOGY / Clinical Psychology